The impact of health insurance on self-protection of Chinese rural residents - Li, Yao; Li, Lei; Liu, Junxia (Frontiers in Public Health, 2022)
Purpose: Health insurance lowers the price of medical services, which reduces the insured’s demand for self-protection (such as, live a healthy lifestyle or invest in disease prevention) that could help reduce the probability of getting sick, then ex ante moral hazard happens. The purpose of this study is to examine the impact and its heterogeneity of health insurance on the self-protection of Chinese rural residents. Method: This study firstly builds a theoretical model of health insurance and self-protection. Then, based on the data from the 2004 to 2015 China Health and Nutrition Survey (CHNS), we adopt ordinary least squares model, probit model and instrumental variable method to empirically investigate the impact of health insurance on Chinese rural residents’ self-protection. Results: After addressing the endogeneity problem, the study finds that participating in health insurance exerts a significant negative impact on the demand for self-protection. Specifically, health insurance participation not only increases residents’ tendency towards drinking liquor by 3.4 per cent, and that of having general obesity by 3.7 per cent, but also reduces residents’ preventive medical expenditure by 1.057%, increasing BMI by 0.784 kg/m2. Further analysis shows that there is heterogeneity between groups, as health insurance participation reduces preventive medical expenditure of people who are female, younger and high-educated, and increases the tendency towards drinking liquor of people who are younger and low-educated. Conclusions: To reduce the impact of ex ante moral hazard induced by health insurance, our findings suggest that it is necessary to improve the disease prevention function of health insurance and introduce a risk adjustment mechanism into the premium or co-payment design of health insurance.